DYNAMICS OF EEG AMPLITUDE AND FREQUENCY CHANGES IN THE LEFT AND RIGHT PARTS OF THE BRAIN IN 17-YEAR-OLD STUDENTS WITH SANGUINE TEMPERAMENT - Rustamova, T.V.; Kazimov, A.Kh. (World of Medicine and Biology, 2024)
The research work was devoted to the change of amplitude and frequency indicators of alpha-, beta-, delta- and theta waves in the left and right brain regions. First of all, students’ temperament type and situational and personal excitement level were studied in the research. the study was conducted on 17-year-old sanguine type students in 3 stages on a regular day, before and after the exam. Our results show that the change of the amplitude of the EEG waves in both sections during the first semester exam in 17-year-old students was on a wavy line. During the examination process, the frequency-amplitude of the waves in the position of waiting for the result was strongly affected by the level of excitement. Due to the emotional tension of the exam process before and after the exam compared to the usual school day, the amplitude rhythms of alpha-, beta-, theta- and delta-waves of EEG in the right and left occipital, occipital, occipital and forehead parts of the cerebral cortex in students with sanguine temperament type a number of different directional regularities in percentage and range of spectral power are obtained.